Terapi Zikir sebagai Intervensi untuk Menurunkan Kecemasan pada Lansia - Tria Widyastuti; Mohammad Abdul Hakim; Salmah Lilik (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
Anxiety is a common problem especially in elderly people. Zikir, a remembrance to God in Islam, is believed in giving a comfort in people. This study examined the zikir as intervention in decreasing anxiety. The elderly people in a nursing home in Surakarta were involved in this study. In the pretest, 37 subjects were selected according to the anxiety score using Geriatric Anxiety Inventory (GAI) and cognitive function score using Mini Mental State Examination (MMSE). A number of 9 elderly people participated in the experiment were grouped ramdomly into experimental and control group. The results of Mann-Whitney test showed a significant difference between pretest and posttest score in both groups (Z = -1.968, p < 0.05). Experimental group showed a significant decrease of anxiety score after intervention. Zikir theraphy as intervention effectively decrease anxiety in elderly people.